Technology for nursing care in a Maternal Intensive Care Unit: a methodological study - Fabíola Nunes de Sá; Jéssica Lourenço Carneiro; Linicarla Fabiole de Souza Gomes; Joselany Afio Caetano; Ana Karina Bezerra Pinheiro; Ana Kelve de Castro Damasceno (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to develop and validate a nursing care plan in a Maternal Intensive Care Unit. Methods: a methodological study, developed in stages: integrative review; Nursing History construction; care plan restructuring; appearance and content validity by judges. Results: the history was organized into sections: Identification; Basic Human Needs; Physical Examination; and Assessment of Basic Human Needs. A care plan was restructured with 34 diagnoses, organized according to basic human needs. A satisfactory level of appearance validity of the history and care plan was obtained (Concordance Index varying between 86.3 and 100 for both instruments), and content validity with average indexes of 90.8 and 92.8, respectively. Thirty-four diagnoses, their interventions and nursing actions were consolidated. Conclusions: the instruments were considered relevant and pertinent in terms of appearance and content, and their use in the institution under study as well as in other similar services may be recommended.